2014
DOI: 10.1117/12.2066483
|View full text |Cite
|
Sign up to set email alerts
|

14-nm photomask simulation sensitivity

Abstract: This study quantifies the impact of systematic mask errors on OPC model accuracy and proposes a methodology to reconcile the largest errors via calibration to the mask error signature in wafer data. First, we examine through simulation, the impact of uncertainties in the representation of photomask properties including CD bias, corner rounding, refractive index, thickness, and sidewall angle. The factors that are most critical to be accurately represented in the model are cataloged. CD bias values are based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In addition, the MAT error and tapered SWA deformation of the absorber are increased by repeated mask cleaning process [12,13]. Recently, Sturtevant et al and Rudolph et al studied the impact of photomask uncertainties on computational lithography [4,14,15]. The results revealed that the variations of MAT and SWA cause significant CD errors (CDEs) that cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the MAT error and tapered SWA deformation of the absorber are increased by repeated mask cleaning process [12,13]. Recently, Sturtevant et al and Rudolph et al studied the impact of photomask uncertainties on computational lithography [4,14,15]. The results revealed that the variations of MAT and SWA cause significant CD errors (CDEs) that cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%